THE EFFECT OF COOPERATIVE SCRIPT MODELON STUDENTS’ READING COMPREHENSION OF DESCRPTIVE TEXT (A STUDY AT THE TENTHGRADE OF SMA NEGERI 1 PADANGBOLAK 2020 – 2021 ACADEMIC YEAR) - Elyana Sari Harahap (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Harahap, Elyana Sari. 2020. The Effect Of Cooperative Script Modelon Students’ Reading Comprehension Of Descriptive Text (A Study at the Tenth Grade of Sma Negeri 1 Padangbolak 2020 – 2021 Academic Year). Skripsi. Program Studi Pendidikan Bahasa Inggris. Institut Pendidikan Tapanuli Selatan. The objective of this research are to know: 1) The application of cooperative script model in teaching reading comprehension of descriptive text, 2) The students’ reading comprehension of descriptive text before and after using cooperative script model, 3) Is any significant effect of cooperative script model on students’ reading comprehension of descriptive text at the tenth grade students of SMA Negeri 1 Padang Bolak. This research used an experimental method with pre-experimental research design; one group pretest-posttest design. The population is all of the tenth grade students which consist of 172 students and the samples are 30 students gotten by using purposive sampling.In collecting the data, the researcher used an observation sheet to get the data of the application of cooperative script model and test to get the data of the students’ reading comprehension of descriptive text. The result of the application of cooperative script model is 3.6, it is categorized “very good”. The mean score of the students’ reading comprehension of descriptive text is 43, it is categorized “fail”. Meanwhile after cooperative script model was 70.05, it is categorized “enough”. The researcher uses statistic process in analyzing the data by using t-test formula. Based on the data that had been analyzed, the result of data analyzing showed that t-test is higher than t-table (t-test 12.35 > t-table 2.04). So, the hypothesis is accepted. It means that there is a significant effect of cooperative script model on students’ reading comprehension of descriptive text at the tenth grade students of SMA Negeri 1 Padang Bolak in 2020/2021 Academic Year. Keyword : Cooperative Script, Reading Descriptive Text